Implementation of Higher Order Thinking Skills In Physical Education Learning In Covid-19 Era: Is It Work? - Festiawan, Rifqi; Khurrohman, Moch Fath (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2021)
This study aims to determine how well the implementation of Higher Order Thinking Skills (HOTS) based on Physical Education at Banyumas Regency in 2020. This type of research is a quantitative descriptive study using a survey method. The population in this study were all physical education teachers in Banyumas Regency, totaling 29 teachers, who were taken using the total sampling technique. The data collection technique used a questionnaire. The data analysis technique used percentage descriptive analysis. The results showed that the implementation of Higher Order Thinking Skills (HOTS) based Physical Education at Banyumas Regency in 2020 was in the "very poor" category of 0.00% (0 teachers), "less" of 51.72% (15 teachers), " enough "by 48.28% (14 teachers)," good "by 0.00% (0 teachers), and "Very good" by 0.00%. From these results, can be concluded that the implementation of Higher Order Thinking Skills (HOTS) based Physical Education at Banyumas Regency in 2020 was less category. This is certainly an evaluation so that the implementation of the 2013 curriculum can be further improved so that learning objectives can be achieved properly.